Educating the phoenix : rescuing children, reuniting families, and saving a school district after the 2018 Paradise, California camp fire - Esping, Amber; Mercer, Jess (Psychological perspectives on contemporary educational issues., 2025)
Educating the Phoenix focuses on the rebuild of an entire school system in the wake of absolute physical devastation and population diaspora from wildfire. When school started on November 8, 2018, the Paradise Unified School District (PUSD) boasted a thriving network of eleven campuses housing 3,401 students and 390 full-time employees. Four hours later, the Camp Fire had reduced three schools to ash, and all PUSD power, communications and maintenance infrastructures were wiped out. The food service warehouse and offices were gone. The transportation office was gone. Seventeen buses were damaged or converted to melted, sooty shells. The remaining eight campuses were in various states of ruin, from smoke damage only (one school and the District Office) to partially or mostly destroyed (seven schools). Nearly all of the students and seventy percent of PUSD employees also lost their homes. Meanwhile, some teachers, bus drivers, administrators, and other school personnel shepherded thousands of children to safety in a small, spontaneous Dunkirk of the Sierra Nevada foothills. Many of their colleagues stayed at the campuses, checking every cranny in every school to make sure no one was left behind. It may be the most dramatic story of in loco parentis ever recorded. California law required that the PUSD shut down, perhaps permanently, but this is not what the students or their parents said they wanted. When PUSD leadership visited with families, the message was clear: These children had already lost nearly everything else that was stable in their lives, and dispersing them to unfamiliar schools would be another blow. They wanted to be together with their friends and their teachers. Hearing this feedback, Superintendent Michelle John O'Neal led the charge to keep the PUSD intact. She prevailed, and many kids came back, even if that meant their first "classroom" was an aisle in an empty hardware store in a nearby city. By the fifth anniversary of the Fire, PUSD had rebuilt a dynamic, fully functioning district with six beautiful campuses and an e-learning academy. This book uses interviews with key personnel to tell the remarkable story of how the people of the PUSD made this happen.